Implementación de un sistema automatizado para el control de temperatura y pH en la yogurtera del CETTEPS. - Moyano Orozco, Karen Lisseth (2025)
At the Center for Technology Transfer of Services and Products (CETTEPS), an automated methodology was introduced to stabilize temperature in yogurt production, aiming to improve product quality and optimize the production process. However, the reliability of data collection, especially regarding temperature during critical stages such as pasteurization and fermentation, is compromised due to inadequate instrument calibration, which compromises the quality of the final product. The methodology is mixed; it begins with a thorough evaluation of the manual system to establish a comparative baseline. From this, the automated system was implemented with a temperature sensor programmed using a PLC (Programmable Logic Controller), and the flow outlets were reorganized. The parameters evaluated in the 6 productions (3 manual and 3 automatic) were: thermal stability at critical points such as pasteurization and fermentation, fermentation time where this parameter was included acidity and pH, microbiology expressed in Aerobic Count and Coliform Count, finally, the shelf life of yogurt in the two systems evaluated by syneresis. The main results showed significant differences between the data groups in the pasteurization stage with a p-value of 4.56 x10-5 and in incubation with a p-value of 1.698 x10-4. On the other hand, the pH drop in the incubation stage was controlled by means of the temperature sensor. Finally, the document shows a basic operation manual that includes precautions, components, mode of use, maintenance and solution of possible problems. In conclusion, the automated system showed significant thermal differences in the critical stages of pasteurization and fermentation, which is reflected in improved product quality. The implementation not only optimized the production process but also represents a significant technological advance in the semi-industrial field of CETTEPS. It is recommended that personnel be trained both hands-on and in the use of the operating manual, as this will prevent accidents for both the operator and the equipment.